Peningkatan Kompetensi Guru Melalui Sinergi Teknologi dan Inkuiri Kolaboratif pada Pembelajaran Mendalam - Nurini Nurini (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Teacher competence is a crucial part of the learning process, as teachers are not merely teaching but also sincerely educating, ensuring meaningful learning. Rapid technological developments and the evolving lives of children require teachers to be adaptive and innovative in enhancing their competencies in the face of environmental and contemporary changes in the learning process. This study aims to determine the extent of teachers' technological mastery and the digital products they can produce through the use of technology in in-depth learning by implementing collaborative inquiry stages in schools. This study is a good practice in schools, using a descriptive qualitative approach. Data collection techniques included observation and interviews. The results showed that teachers' technological mastery was 91.3%, and innovative digital products produced by teachers were 89.8%. This indicates a high and good level of teacher competency achievement. Therefore, integrating a collaborative inquiry framework with in-depth learning objectives, supported by the use of digital media, is an effective strategy for improving teacher competency. It is hoped that as teachers' challenges increase, competency improvement will be even more optimal, enabling educational goals, both at school and nationally, to be realized and the national ideal of quality education for all